Dysfunction of the blood-brain barrier in postoperative delirium patients, referring to the axonal damage biomarker phosphorylated neurofilament heavy subunit - Mietani, Kazuhito (PLoS One, 2019)
BACKGROUND: Delirium is the most common postoperative complication of the central nervous system (CNS) that can trigger long-term cognitive impairment. Its underlying mechanism is not fully understood, but the dysfunction of the blood-brain barrier (BBB) has been implicated. The serum levels of the axonal damage biomarker, phosphorylated neurofilament heavy subunit (pNF-H) increase in moderate to severe delirium patients, indicating that postoperative delirium can induce irreversible CNS damage. Here, we investigated the relationship among postoperative delirium, CNS damage and BBB dysfunction, using pNF-H as reference. METHODS: Blood samples were collected from 117 patients within 3 postoperative days. These patients were clinically diagnosed with postoperative delirium using the Confusion Assessment Method for the Intensive Care Unit. We measured intercellular adhesion molecule-1, platelet and endothelial cell adhesion molecule-1, vascular cell adhesion molecule-1, E-selectin, and P-selectin as biomarkers for BBB disruption, pro-inflammatory cytokines (tumor necrosis factor-alpha, interleukin-1 beta, interleukin-6), and pNF-H. We conducted logistic regression analysis including all participants to identify independent biomarkers contributing to serum pNF-H detection. Next, by multiple regression analysis with a stepwise method we sought to determine which biomarkers influence serum pNF-H levels, in pNF-H positive patients. RESULTS: Of the 117 subjects, 41 were clinically diagnosed with postoperative delirium, and 30 were positive for serum pNF-H. Sensitivity and specificity of serum pNF-H detection in the patients with postoperative delirium were 56% and 90%, respectively. P-selectin was the only independent variable to associate with pNF-H detection (P < 0.0001) in all 117 patients. In pNF-H positive patients, only PECAM-1 was associated with serum pNF-H levels (P = 0.02). CONCLUSIONS: Serum pNF-H could be an objective delirium biomarker, superior to conventional tools in clinical settings. In reference to pNF-H, P-selectin may be involved in the development of delirium-related CNS damage and PECAM-1 may contribute to the progression of delirium- related CNS damage.